Antigenic and phylogenetic relationships of outer capsid protein VP2, from multiple bluetongue virus serotypes - Fay, Petra Christel (2018)
Bluetongue (BT) is a non-contagious arthropod transmitted virus that infects ruminants including sheep, cattle and goats. Bluetongue virus (BTV) is economically important due to the severity of disease in naïve animals and the financial cost of the development and implementation of effective vaccines and diagnostic tests, and restrictions on animal movements and trade.